Fabrication, properties and applications of polymer composites additively manufactured with filler alignment control: A review. (1st May 2023) - Markandan, Kalaimani; Lai, Chang Quan
Abstract: Interest in additive manufacturing (AM) of polymers has intensified significantly in recent years as various industrial and research sectors begin to recognize the benefits of the technology, which include easy customization, reduced material wastage and short turnaround times. As demand for AM parts start to shift from prototypes to end products, there is an increasing impetus to improve the performance of 3D printed polymers. In response, recent studies have begun to explore ways to reinforce polymer matrices through the incorporation and alignment of fillers during the additive manufacturing process. Here, a review of the recent advances in 3D printing techniques for polymer composites has been conducted and analyzed, specifically for their ability to control the alignment and arrangement of discontinuous fillers, as well as other benefits and disadvantages associated with their operations. Common analytical models that are currently used to relate the microstructures of these composites to the macroscopic mechanical properties of the 3D printed parts are presented and discussed. The functional properties and applications of these materials are also briefly summarized. Graphical abstract: Image 1